Captopril in combination with hydrochlorothiazide: Comparative efficacy vs perceived best therapy - Holzgreve, H. (1987)
1 An open, randomized, multicentre, comparative trial on 2128 patients with mild-to-moderate hypertension, treated with so-called perceived best therapy or a combination of captopril plus hydrochlorothiazide (HCTZ), was conducted over a period of 10 weeks. 2 Both regimens lead to significant blood pressure reductions within the initial 6 weeks, with a difference of 3 mmHg systolic and 2 mmHg diastolic in favour of the captopril plus HCTZ regimen as compared to the perceived best therapy. 3 Both an increase in the daily dose of captopril in uncontrolled patients receiving initial treatment with captopril plus HCTZ and treatment with captopril plus HCTZ in uncontrolled patients receiving the perceived best therapy was followed by improved blood pressure control. 4 There were more withdrawals mainly due to side effects and non-compliance in the captopril plus HCTZ group as compared to the perceived best therapy group. 5 By contrast, there were fewer side effects and a tendency towards a more pronounced improvement of complaints and general well-being in the captopril plus HCTZ group. 6 The study has yielded no clear evidence of an increased number of side effects known to be associated with captopril. 7 Changes of the treatment regimen and dosages according to diastolic blood pressure during the study are difficult to achieve in a study of this type and size.